Resin composition

By using epoxy resin, active ester curing agent, aromatic polyester polyol resin and inorganic filler in the resin composition, the dielectric loss tangent, excellent adhesion and contamination in the multi-layer printed wiring board are solved. The problem of difficult removal is achieved, and high-performance insulating layer and conduction reliability are achieved.

CN112778699BActive Publication Date: 2025-01-10AJINOMOTO CO INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202011238318.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-11
Filing Date
2020-11-09
Publication Date
2025-01-10
Estimated Expiration
2040-11-09

AI Technical Summary

Technical Problem

The prior art is difficult to provide resin compositions with low dielectric loss tangent, excellent adhesion and excellent stain removal when manufacturing multi-layer printed wiring boards, and cannot meet the high performance requirements of conduction reliability and insulating layers at the same time.

Method used

Using a resin composition containing epoxy resin, active ester curing agent, polyester polyol resin with aromatic structure and inorganic filler material, the dielectric loss tangent is formed by optimizing the component ratio and process conditions. , cured substance with excellent stain removal.

Benefits of technology

It realizes an insulating layer with low dielectric loss tangent, excellent adhesion and excellent stain removal. It is suitable for the manufacturing of multi-layer printed wiring boards and semiconductor devices, and improves conduction reliability and insulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002767528210000281
    Figure BDA0002767528210000281
Patent Text Reader

Abstract

The present invention aims to provide: a resin composition that can produce a cured product having low dielectric loss tangent, excellent adhesion, and excellent stain removal properties; a resin sheet containing the resin composition; a printed wiring board having an insulating layer formed using the resin composition; and a semiconductor device. The solution of the present invention is a resin composition comprising: (A) an epoxy resin, (B) an active ester curing agent, (C) a polyester polyol resin having an aromatic structure, and (D) an inorganic filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition and further to a resin sheet, a printed wiring board and a semiconductor device containing the resin composition. Background Art

[0002] As a manufacturing technology for printed wiring boards, a manufacturing method based on a build-up method in which an insulating layer and a conductive layer are alternately stacked on an inner layer circuit substrate is known. The insulating layer can generally be formed by curing a resin composition.

[0003] For example, Patent Document 1 describes a thermosetting resin composition containing (A) a thermosetting resin, (B) a thermosetting agent, and (C) a modified resin. In addition, Patent Document 2 describes an active energy ray-curable composition containing an epoxy (meth)acrylate resin containing an acid group, an epoxy curing agent, and a modified resin. In addition, Patent Document 3 describes a curable resin composition containing (A) an epoxy resin, (B) an active ester curing agent and / or a cyanate curing agent, and (C) a polyester resin having a fluorene structure.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2019 / 131413

[0007] Patent Document 2: International Publication No. 2019 / 044803

[0008] Patent document 3: Japanese Patent Application Publication No. 2014-159512. Summary of the invention

[0009] Problems to be solved by the invention

[0010] In recent years, when manufacturing multilayer printed wiring boards, cured products of resin compositions for forming insulating layers are required to have low dielectric loss tangent and high adhesion to copper foil, etc., as well as smear removability for ensuring conduction reliability.

[0011] The present inventors have conducted research and found that the cured product of a resin composition containing a material that reduces dielectric loss tangent and improves adhesion has low contamination removability for ensuring conduction reliability. Therefore, it is currently impossible to provide a resin composition that has low dielectric loss tangent, excellent adhesion, and excellent contamination removability.

[0012] The present invention aims to provide a resin composition capable of obtaining a cured product having low dielectric loss tangent, excellent adhesion and excellent stain removability; a resin sheet containing the resin composition; a printed wiring board having an insulating layer formed using the resin composition; and a semiconductor device.

[0013] Means for solving problems

[0014] The present inventors have conducted intensive research to solve the aforementioned problems, and as a result, have found that the aforementioned problems can be solved by a resin composition comprising (A) an epoxy resin, (B) an active ester curing agent, (C) a polyester polyol resin having an aromatic structure, and (D) an inorganic filler in combination, thereby completing the present invention. That is, the present invention includes the following contents.

[0015] [1] A resin composition comprising:

[0016] (A) Epoxy resin,

[0017] (B) active ester curing agent,

[0018] (C) a polyester polyol resin having an aromatic structure, and

[0019] (D) Inorganic filling materials;

[0020] [2] The resin composition according to [1], wherein the content of the component (C) is 0.1% by mass or more and 10% by mass or less, when the non-volatile component in the resin composition is 100% by mass;

[0021] [3] The resin composition according to [1] or [2], wherein the component (C) has a bisphenol skeleton;

[0022] [4] The resin composition according to [3], wherein the component (C) has a hydroxyl group at a terminal;

[0023] [5] The resin composition according to any one of [1] to [4], wherein the hydroxyl value of the component (C) is 2 mgKOH / g or more and 450 mgKOH / g or less;

[0024] [6] The resin composition according to any one of [1] to [5], wherein the viscosity of the component (C) at 75°C is 0.5 Pa·s or more and 25 Pa·s or less;

[0025] [7] The resin composition according to any one of [1] to [6], wherein the number average molecular weight of component (C) is 500 or more and 7000 or less;

[0026] [8] The resin composition according to any one of [1] to [7], wherein the component (B) comprises at least one selected from the group consisting of a dicyclopentadiene-type active ester curing agent and a naphthalene-type active ester curing agent;

[0027] [9] The resin composition according to any one of [1] to [8], wherein, when b1 is the content of the component (B) when the non-volatile components in the resin composition are 100% by mass, and c1 is the content of the component (C) when the non-volatile components in the resin composition are 100% by mass, b1 / c1 is 3 or more and 30 or less;

[0028]

[10] The resin composition according to any one of [1] to [9], wherein the content of the component (D) is 50% by mass or more when the non-volatile component in the resin composition is 100% by mass;

[0029]

[11] The resin composition according to any one of [1] to

[10] , further comprising (E) a curing agent;

[0030]

[12] The resin composition according to

[11] , wherein the curing agent (E) comprises a phenol curing agent;

[0031]

[13] The resin composition according to any one of [1] to

[12] , which is used for insulation purposes;

[0032]

[14] The resin composition according to any one of [1] to

[13] , which is used for forming an insulating layer;

[0033]

[15] The resin composition according to any one of [1] to

[14] , which is used to form an insulating layer, wherein the insulating layer is an insulating layer for forming a conductor layer;

[0034]

[16] A resin sheet comprising: a support, and a resin composition layer provided on the support and comprising the resin composition described in any one of [1] to

[15] ;

[0035]

[17] A printed wiring board comprising an insulating layer formed using a cured product of the resin composition described in any one of [1] to

[15] .

[0036]

[18] A semiconductor device comprising the printed wiring board described in

[17] .

[0037] Effects of the Invention

[0038] The present invention can provide a resin composition that can produce a cured product having low dielectric loss tangent, excellent adhesion, and excellent stain removability; a resin sheet containing the resin composition; a printed wiring board having an insulating layer formed using the resin composition; and a semiconductor device. DETAILED DESCRIPTION

[0039] The present invention will be described in detail below by showing embodiments and examples, but the present invention is not limited to the embodiments and examples listed below, and can be implemented with any changes within the scope of the claims and their equivalents.

[0040] [Resin composition]

[0041] The resin composition of the present invention is a resin composition comprising (A) an epoxy resin, (B) an active ester curing agent, (C) a polyester polyol resin having an aromatic structure, and (D) an inorganic filler. By using such a resin composition, a cured product having excellent stain removal properties, low dielectric loss tangent, and excellent adhesion can be obtained.

[0042] The resin composition may further include any component in addition to the components (A) to (D). Examples of the arbitrary component include (E) a curing agent, (F) a thermoplastic resin, (G) a curing accelerator, and (H) other additives. The components included in the resin composition are described in detail below.

[0043] <(A) Epoxy resin>

[0044] Examples of the epoxy resin (A) include bixylenol epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins. Resins, glycidylamine epoxy resins, glycidyl ester epoxy resins, cresol novolac epoxy resins, biphenyl epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, epoxy resins containing spiro rings, cyclohexane epoxy resins, cyclohexanedimethanol epoxy resins, naphthylene ether epoxy resins, trimethylol epoxy resins, tetraphenylethane epoxy resins, etc. The epoxy resins may be used alone or in combination of two or more.

[0045] The resin composition preferably contains an epoxy resin having two or more epoxy groups in one molecule as the epoxy resin (A). From the viewpoint of significantly obtaining the desired effect of the present invention, the proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more relative to 100% by mass of the non-volatile component of the epoxy resin (A).

[0046] Epoxy resins include epoxy resins that are liquid at a temperature of 20°C (hereinafter, sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter, sometimes referred to as "solid epoxy resins"). For the resin composition, as (A) epoxy resin, only liquid epoxy resins may be included, or only solid epoxy resins may be included, but it is preferred to include liquid epoxy resins and solid epoxy resins in combination. By using a liquid epoxy resin and a solid epoxy resin in combination as (A) epoxy resin, sufficient flexibility can be obtained when used in the form of a resin sheet, or the fracture strength of the cured product of the resin composition can be increased.

[0047] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.

[0048] As liquid epoxy resins, preferred are bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexanedimethanol type epoxy resins, glycidyl amine type epoxy resins, and epoxy resins having a butadiene structure, and bisphenol A type epoxy resins and bisphenol F type epoxy resins are more preferred.

[0049] Specific examples of liquid epoxy resins include: "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "EPIKOTE828EL" (bisphenol A-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" (glycidylamine-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ZX1059" (a mixture of bisphenol A-type epoxy resin and bisphenol F-type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemicals; "EX-721" (glycidyl ester-type epoxy resin) manufactured by Nagase ChemteX; and "Celloxide 2021P" (alicyclic epoxy resin with an ester skeleton); "PB-3600" manufactured by Daicel Corporation (epoxy resin with a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., etc. They can be used alone or in combination of two or more.

[0050] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferred.

[0051] As the solid epoxy resin, preferred are biphenylol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin, and more preferred are naphthol type epoxy resin and biphenyl type epoxy resin.

[0052] Specific examples of solid epoxy resins include: "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation; and "HP-7200" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation. "HP-7200HH", "HP-7200H", "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. ”, “NC3000”, “NC3000L”, “NC3100” (biphenyl type epoxy resin); “ESN475V” (naphthol type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; “ESN485” (naphthol novolac type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; “YX4000H”, “YX4000”, “YL6121” (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; “YX4000HK” (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation "YL7760" (bisphenol AF type epoxy resin) made by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) made by Mitsubishi Chemical Corporation; "jER1010" (solid bisphenol A type epoxy resin) made by Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) made by Mitsubishi Chemical Corporation, etc. These can be used alone or in combination of two or more.

[0053] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin (A), their amount ratio (liquid epoxy resin: solid epoxy resin) is preferably 1:0.1 to 1:20, more preferably 1:1 to 1:10, and particularly preferably 1:1.5 to 1:5 in terms of mass ratio. By making the amount ratio of the liquid epoxy resin to the solid epoxy resin within the above range, the desired effect of the present invention can be significantly obtained. In addition, usually, when used in the form of a resin sheet, moderate adhesion can be achieved. In addition, usually, when used in the form of a resin sheet, sufficient flexibility can be obtained and the handleability is improved. In addition, usually, a cured product with sufficient breaking strength can be obtained.

[0054] The epoxy equivalent of the (A) epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further more preferably 110 g / eq. to 1000 g / eq. By being within the above range, the crosslinking density of the cured product of the resin composition layer becomes sufficient, and an insulating layer with a small surface roughness can be formed. The epoxy equivalent is the mass of the epoxy resin containing 1 equivalent of epoxy groups. The epoxy equivalent can be measured according to JIS K7236.

[0055] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the epoxy resin (A) is preferably 100 to 5000, more preferably 100 to 4000, and even more preferably 200 to 5000. The weight average molecular weight of the resin can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).

[0056] For the content of (A) epoxy resin, from the viewpoint of obtaining an insulating layer showing good mechanical strength and insulation reliability, when the non-volatile component in the resin combination is set to 100 mass %, it is preferably more than 1 mass %, more preferably more than 5 mass %, and further preferably more than 10 mass %. For the upper limit of the content of epoxy resin, from the viewpoint of significantly obtaining the desired effect of the present invention, it is preferably less than 25 mass %, more preferably less than 20 mass %, and particularly preferably less than 15 mass %. It should be noted that in the present invention, as long as it is not clearly stated separately, the content of each component in the resin combination is the value when the non-volatile component in the resin combination is set to 100 mass %.

[0057] <(B) Active ester curing agent>

[0058] The resin composition contains (B) an active ester curing agent. When an active ester curing agent is used, generally, the dielectric loss tangent can be reduced and the adhesion becomes excellent, but on the other hand, the stain removal property is poor. However, for the resin composition of the present invention, since the (B) active ester curing agent is included in combination with the (C) component, a cured product that can reduce the dielectric loss tangent, has excellent adhesion, and is also excellent in stain removal can be obtained. The (B) component can be used alone or in combination of two or more.

[0059] As (B) active ester curing agent, usually, it is preferred to use esters of phenolic esters, thiophenolic esters, N-hydroxylamine esters, heterocyclic hydroxy compounds, etc., which have ester groups with more than 2 high reactive activities in 1 molecule. The active ester curing agent is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. Especially from the viewpoint of improving heat resistance, it is preferred to obtain an active ester curing agent from a carboxylic acid compound and a hydroxy compound, and more preferably an active ester curing agent from a carboxylic acid compound and a phenolic compound and / or a naphthol compound. As a carboxylic acid compound, for example, benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be cited. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, and phenol novolac. Here, the so-called "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol on one molecule of dicyclopentadiene.

[0060] Specifically, as component (B), preferably, dicyclopentadiene type active ester curing agent, naphthalene type active ester curing agent containing naphthalene structure, active ester curing agent containing acetylated product of phenol novolac, active ester curing agent containing benzoylated product of phenol novolac, wherein, more preferably, at least one selected from dicyclopentadiene type active ester curing agent and naphthalene type active ester curing agent, further preferably, dicyclopentadiene type active ester curing agent. As dicyclopentadiene type active ester curing agent, preferably, active ester curing agent containing dicyclopentadiene type diphenol structure. So-called "dicyclopentadiene type diphenol structure" means a divalent structural unit formed by phenylene-dicyclopentylene (dicyclopentylene)-phenylene.

[0061] Examples of commercially available active ester curing agents (B) include "EXB9451" (manufactured by DIC Corporation, with an active ester group equivalent of 223), "EXB9460" (manufactured by DIC Corporation, with an active ester group equivalent of 223), "EXB9460S" (manufactured by DIC Corporation, with an active ester group equivalent of 223), "HPC-8000-65T" (manufactured by DIC Corporation, with an active ester group equivalent of 223), "HPC-8000H-65TM" (manufactured by DIC Corporation, with an active ester group equivalent of 223) as active ester curing agents containing a dicyclopentadiene-type diphenol structure. C company, active ester equivalent of 224), "HPC-8000L-65TM" (DIC company, active ester equivalent of 220); "EXB-8100L-65T" (DIC company, active ester equivalent of 234), "EXB8150-60T" (DIC company, active ester equivalent of 226), "EXB9416-70BK" (DIC company, active ester equivalent of 274), "PC1300-02" (Air "EXB9401" (manufactured by DIC Corporation, with an active ester equivalent of 307) as an active ester curing agent containing phosphorus; "DC808" (manufactured by Mitsubishi Chemical Corporation, with an active ester equivalent of 149) as an active ester curing agent that is an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester curing agents that are benzoylated products of phenol novolac, etc.

[0062] The active ester group equivalent of the active ester curing agent (B) is preferably 50 g / eq. to 500 g / eq., more preferably 50 g / eq. to 400 g / eq., and even more preferably 100 g / eq. to 300 g / eq., from the viewpoint of obtaining a cured product having a reduced dielectric loss tangent and excellent adhesion. The active ester group equivalent is the mass of the active ester curing agent containing 1 equivalent of active ester groups.

[0063] The amount ratio of (A) epoxy resin to (B) active ester curing agent is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.3 to 1:3, and even more preferably 1:0.5 to 1:2, in terms of the ratio of [the total number of epoxy groups of the epoxy resin]:[the total number of active groups of the active ester curing agent]. Here, the "number of epoxy groups of the epoxy resin" refers to the value obtained by adding up all the values ​​obtained by dividing the mass of the non-volatile components of the epoxy resin present in the resin composition by the epoxy equivalent. In addition, the "number of active groups of the active ester curing agent" refers to the value obtained by adding up all the values ​​obtained by dividing the mass of the non-volatile components of the active ester curing agent present in the resin composition by the active ester group equivalent. By making the amount ratio of the epoxy resin to the active ester curing agent within the above range, the effect of the present invention can be significantly obtained.

[0064] For the content of (B) active ester curing agent, when the non-volatile component in the resin combination is set to 100 mass %, it is preferably more than 1 mass %, more preferably more than 3 mass %, and more preferably more than 5 mass %. In addition, the upper limit is preferably less than 30 mass %, more preferably less than 20 mass %, and more preferably less than 15 mass %. By making the content of (B) component within the above range, a cured product that can reduce dielectric loss tangent and excellent adhesion can be obtained.

[0065] <(C) Polyester polyol resin having an aromatic structure>

[0066] The resin composition contains (C) a polyester polyol resin having an aromatic structure as the component (C). The resin composition of the present invention contains the components (B) and (C) in combination, and thus can obtain a cured product having a low dielectric loss tangent, excellent adhesion, and excellent stain removal properties.

[0067] From the viewpoint of improving the adhesion with the conductor layer such as copper foil and then improving the hydrolyzability, the (C) component is preferably a resin having a structure from polyester and a structure from polyol. The resin can be obtained, for example, by reacting a polyol with a polycarboxylic acid. The (C) component can be used alone or in combination with two or more. In addition, as the (C) component, it is preferred that an aromatic structure is present in any one of the structures from polyester and the structure from polyol. From the viewpoint of significantly obtaining the effect of the present invention, it is more preferred that a bisphenol skeleton is present in any one of the structures from polyester and the structure from polyol, and it is further preferred that a bisphenol skeleton is present in the structure from polyol. The so-called aromatic structure is a chemical structure generally defined as an aromatic, and also includes polycyclic aromatics and aromatic heterocycles. As the bisphenol skeleton, for example, a bisphenol A skeleton, a bisphenol B skeleton, a bisphenol C skeleton, a bisphenol AF skeleton, etc. can be cited, preferably a bisphenol A skeleton.

[0068] For component (C), from the viewpoint of improving compatibility with epoxy resin (A) and adhesion with copper foil, etc., it is preferred that the terminal of the molecular chain of component (C) has a hydroxyl group. The number of hydroxyl groups contained in component (C) is preferably 2 or more, preferably 6 or less, more preferably 4 or less, further preferably 3 or less, and particularly preferably 2 per molecule.

[0069] Examples of the polyol include aliphatic polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, and 1,3-butanediol; polyols having an alicyclic structure such as cyclohexanedimethanol; polyols having an aromatic structure such as a bisphenol skeleton such as bisphenol A and bisphenol F; and polyols obtained by modifying the aforementioned polyols having an aromatic structure with alkylene oxide. Among them, polyols preferably include polyols having an alicyclic structure, polyols having an aromatic structure, and polyols obtained by modifying a polyol having an aromatic structure with alkylene oxide, and more preferably polyols obtained by modifying a polyol having an aromatic structure with alkylene oxide. One type of the polyol may be used alone, or two or more types may be used in combination.

[0070] Examples of alkylene oxides that can be used for modification of polyols having an aromatic structure include alkylene oxides having 2 or more carbon atoms such as ethylene oxide and propylene oxide. The upper limit of the carbon number of the alkylene oxide having 2 or more carbon atoms is preferably 4 or less, more preferably 3 or less.

[0071] The number average molecular weight of the polyol is preferably 50 or more, preferably 1500 or less, more preferably 1000 or less, and further preferably 700 or less.

[0072] A commercially available product may be used as the polyol. Examples of the commercially available product include "HYPROX MDB-561" manufactured by DIC Corporation.

[0073] Examples of the polycarboxylic acid include aliphatic polycarboxylic acids such as succinic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid; aromatic polycarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalene dicarboxylic acid; and anhydrides and esters thereof.

[0074] The polycarboxylic acid may be used alone or in combination of two or more. As the polycarboxylic acid, an aliphatic polycarboxylic acid is preferably included. The content of the aliphatic polycarboxylic acid is preferably 5 mol % or more, more preferably 10 mol % or more, and preferably 100 mol % or less in the total content of the polycarboxylic acid.

[0075] In a preferred embodiment, as the polycarboxylic acid, an aliphatic polycarboxylic acid and an aromatic polycarboxylic acid are used in combination. As the content ratio of the aromatic polycarboxylic acid and the aliphatic polycarboxylic acid (aromatic polycarboxylic acid / aliphatic polycarboxylic acid), on a molar basis, it is preferably 1 / 99 or more, more preferably 30 / 70 or more, further preferably 50 / 50 or more, preferably 99 / 1 or less, more preferably 90 / 10 or less, and further preferably 85 / 15 or less. By making the content ratio of the aromatic polycarboxylic acid and the aliphatic polycarboxylic acid within the above range, the effect of the present invention can be significantly obtained.

[0076] The component (C) may contain an oxyalkylene unit having 4 or more carbon atoms to the extent that the purpose of the present invention is not impaired. The content of the oxyalkylene unit having 4 or more carbon atoms is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 3% by mass or less, and particularly preferably 1% by mass or less.

[0077] The component (C) can be produced, for example, by reacting a polyol with a polycarboxylic acid. The reaction temperature is preferably 190° C. or higher, more preferably 200° C. or higher, preferably 250° C. or lower, more preferably 240° C. or lower. The reaction time is preferably 1 hour or longer, preferably 100 hours or shorter.

[0078] During the reaction, a catalyst may be used as needed. Examples of the catalyst include titanium catalysts such as tetraisopropyl titanate and tetrabutyl titanate; tin catalysts such as dibutyltin oxide; and organic sulfonic acid catalysts such as p-toluenesulfonic acid. The catalyst may be used alone or in combination of two or more.

[0079] From the viewpoint of efficiently proceeding the reaction, the content of the catalyst is preferably 0.0001 parts by mass or more, more preferably 0.0005 parts by mass or more, and preferably 0.01 parts by mass or less, more preferably 0.005 parts by mass or less, based on 100 parts by mass of the total of the polyol and the polycarboxylic acid.

[0080] The hydroxyl value of the component (C) is preferably 2 mgKOH / g or more, more preferably 4 mgKOH / g or more, further preferably 6 mgKOH / g or more, 10 mgKOH / g or more, 25 mgKOH / g or more, 30 mgKOH / g or more, or 35 mgKOH / g or more, and is preferably 450 mgKOH / g or less, more preferably 100 mgKOH / g or less, further preferably 50 mgKOH / g or less, 45 mgKOH / g or less, or 40 mgKOH / g or less, from the viewpoint of significantly obtaining the effects of the present invention.

[0081] The viscosity of the component (C) at 75°C is preferably 0.5 Pa·s or more, more preferably 1 Pa·s or more, further preferably 2 Pa·s or more, 5 Pa·s or more, or 10 Pa·s or more, and preferably 25 Pa·s or less, more preferably 20 Pa·s or less, and further preferably 15 Pa·s or less, from the viewpoint of significantly obtaining the effects of the present invention. The viscosity can be measured using, for example, an E-type viscometer.

[0082] The number average molecular weight of the component (C) is preferably 500 or more, more preferably 1000 or more, further preferably 1500 or more, 2000 or more, or 2500 or more, and is preferably 7000 or less, more preferably 6000 or less, and further preferably 5000 or less, from the viewpoint of improving compatibility with the epoxy resin (A) and adhesion with copper foil, etc. The number average molecular weight is a value calculated based on the hydroxyl value.

[0083] The glass transition temperature of the component (C) is preferably -100°C or higher, more preferably -80°C or higher, and further preferably -70°C or higher, and is preferably 50°C or lower, more preferably 40°C or lower, and further preferably 30°C or lower, from the viewpoint of significantly obtaining the effects of the present invention. The glass transition temperature is a value measured by DSC (differential scanning calorimetry).

[0084] From the viewpoint of significantly obtaining the effects of the present invention, the content of the component (C) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, further preferably 1% by mass or more, and preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 3% by mass or less, or 1.5% by mass or less, based on 100% by mass of the nonvolatile component in the resin composition.

[0085] When the content of the component (B) when the non-volatile component in the resin composition is 100% by mass is b1, and the content of the component (C) when the non-volatile component in the resin composition is 100% by mass is c1, b1 / c1 is preferably 3 or more, more preferably 4 or more, and further preferably 5 or more, and is preferably 30 or less, more preferably 20 or less, and further preferably 15 or less. By setting b1 / c1 within the above range, a cured product can be obtained that can reduce the dielectric loss tangent, has excellent adhesion, and is also excellent in stain removability.

[0086] <(D) Inorganic fillers>

[0087] The resin composition contains (D) an inorganic filler. By containing (D) an inorganic filler in the resin composition, a cured product having a low dielectric loss tangent, excellent adhesion, and excellent stain removability can be obtained.

[0088] As the material of the inorganic filler, an inorganic compound is used. As examples of the material of the inorganic filler, silicon dioxide, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium phosphotungstate, etc., can be cited. Among these, silicon dioxide is particularly preferred. As silicon dioxide, for example, amorphous silicon dioxide, fused silica, crystalline silicon dioxide, synthetic silicon dioxide, hollow silicon dioxide, etc. can be cited. In addition, as silicon dioxide, spherical silicon dioxide is preferred. (D) The inorganic filler can be used alone or in combination of two or more.

[0089] Commercially available products of (D) inorganic fillers include, for example: "UFP-30" manufactured by Denka Chemical Industry Co., Ltd.; "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Corporation; "YC100C", "YA050C", "YA050C-MJE" and "YA010C" manufactured by Admatechs; "UFP-30" manufactured by Denka; "Silfil NSS-3N", "Silfil NSS-4N" and "Silfil NSS-5N" manufactured by Tokuyama Co., Ltd.; "SC2500SQ", "SO-C4", "SO-C2" and "SO-C1" manufactured by Admatechs; and the like.

[0090] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the inorganic filler (D) is preferably 0.01 μm or more, more preferably 0.05 μm or more, particularly preferably 0.1 μm or more, preferably 5 μm or less, more preferably 2 μm or less, and further preferably 1 μm or less.

[0091] (D) The average particle size of the inorganic filler can be measured by the laser diffraction scattering method based on Mie scattering theory. Specifically, it can be measured in the following manner: using a laser diffraction scattering particle size distribution measuring device, the particle size distribution of the inorganic filler is made on a volume basis, and the median particle size is used as the average particle size. The sample can be measured using a sample obtained in the following manner: 100 mg of inorganic filler and 10 g of methyl ethyl ketone are weighed into a vial and dispersed for 10 minutes using ultrasound. For the sample, a laser diffraction particle size distribution measuring device is used, and the wavelength of the light source used is set to blue and red. The particle size distribution of the volume basis of the inorganic filler (D) is measured in a flow cell (flowcell) manner, and the average particle size is calculated from the obtained particle size distribution as the median particle size. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba, Ltd. can be cited.

[0092] From the viewpoint of significantly achieving the desired effect of the present invention, the specific surface area of ​​the inorganic filler (D) is preferably 1 m 2 / g or more, more preferably 2m 2 / g or more, particularly preferably 3m 2 There is no particular upper limit, but it is preferably 60 m 2 / g or less, 50m 2 / g or below or 40m 2 The specific surface area can be obtained by adsorbing nitrogen on the surface of the sample using a specific surface area measuring apparatus (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method and calculating the specific surface area using the BET multipoint method.

[0093] For (D) inorganic filler, from the viewpoint of improving moisture resistance and dispersibility, it is preferably treated with a surface treatment agent. As the surface treatment agent, for example, fluorine-containing silane coupling agent, aminosilane coupling agent, epoxy silane coupling agent, mercapto silane coupling agent, silane coupling agent, alkoxy silane, organosilazane compound, titanate coupling agent, etc. can be cited. In addition, the surface treatment agent can be used alone or in combination of two or more.

[0094] Commercially available products of the surface treatment agent include, for example, “KBM403” (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM803” (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBE903” (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM573” (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “SZ-31” (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM103” (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM-4803” (long-chain epoxy-type silane coupling agent) manufactured by Shin-Etsu Chemical Co., Ltd., and “KBM-7103” (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.

[0095] From the viewpoint of improving the dispersibility of the inorganic filler, it is preferred that the degree of surface treatment based on the surface treatment agent is limited within a specified range. Specifically, for 100 parts by mass of the inorganic filler, it is preferred that 0.2 to 5 parts by mass of the surface treatment agent be used for surface treatment, preferably 0.2 to 3 parts by mass, preferably 0.3 to 2 parts by mass.

[0096] The degree of surface treatment by the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is preferably 0.02 mg / m 2 More preferably 0.1 mg / m 2 More preferably, 0.2 mg / m 2 On the other hand, from the viewpoint of suppressing the increase of the melt viscosity of the resin varnish and the melt viscosity in the sheet form, 1 mg / m 2 Below, more preferably 0.8 mg / m 2 Below, more preferably 0.5 mg / m 2 the following.

[0097] The amount of carbon per unit surface area of ​​the inorganic filler can be measured after washing the surface-treated inorganic filler with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent can be added to the inorganic filler surface-treated with a surface treatment agent, and ultrasonic washing is performed at 25°C for 5 minutes. The supernatant is removed, the solid component is dried, and then the amount of carbon per unit surface area of ​​the inorganic filler is measured using a carbon analyzer. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd. can be used.

[0098] From the viewpoint of significantly obtaining the effects of the present invention, the content of the inorganic filler is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 75% by mass or less, when the non-volatile component in the resin composition is set to 100% by mass.

[0099] <(E) Curing agent>

[0100] For the resin composition, in addition to including the above-mentioned components, as an arbitrary component, (E) curing agent may be further included. Wherein, (B) active ester curing agent is not included in the (E) curing agent. As (E) curing agent, for example, phenol curing agent, naphthol curing agent, benzoxazine curing agent, cyanate curing agent, and carbodiimide curing agent can be cited. Wherein, from the viewpoint of improving insulation reliability, (E) curing agent is preferably any one or more of phenol curing agent, naphthol curing agent, cyanate curing agent, and carbodiimide curing agent, more preferably any of phenol curing agent and naphthol curing agent, and further preferably includes phenol curing agent. (E) curing agent can be used alone or in combination of two or more.

[0101] As the phenolic curing agent and the naphthol curing agent, from the viewpoint of heat resistance and water resistance, a phenolic curing agent having a novolac structure or a naphthol curing agent having a novolac structure is preferred. In addition, from the viewpoint of adhesion with the conductor layer, a nitrogen-containing phenolic curing agent is preferred, and a phenolic curing agent containing a triazine skeleton is more preferred.

[0102] Specific examples of phenol-based curing agents and naphthol-based curing agents include: "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemicals, "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumitomo Chemicals Corporation, and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA3018-50P", and "EXB-9500" manufactured by DIC Corporation.

[0103] Specific examples of the benzoxazine-based curing agent include "HFB2006M" manufactured by Showa High Molecular Co., Ltd. and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0104] Examples of the cyanate curing agent include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylidene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by partially triazinizing these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate resins), "ULL-950S" (multifunctional cyanate resin), "BA230", "BA230S75" (prepolymers obtained by triazine-forming a part or all of bisphenol A dicyanate to form a trimer) manufactured by Lonza Japan Co., Ltd.

[0105] Specific examples of the carbodiimide-based curing agent include "V-03" and "V-07" manufactured by Nisshinbo Chemical Co., Ltd.

[0106] When a curing agent is contained as the component (E), the ratio of the amount of the epoxy resin to the (B) active ester curing agent and the (E) curing agent is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.3 to 1:3, and even more preferably 1:0.5 to 1:2, in terms of [the total number of epoxy groups of the epoxy resin]:[the total number of active groups of the (B) active ester curing agent and the (E) curing agent]. Here, the "number of epoxy groups of the epoxy resin" is the value obtained by adding up all the values ​​obtained by dividing the mass of the non-volatile components of the epoxy resin present in the resin composition by the epoxy equivalent. In addition, the "number of active groups of the (B) active ester curing agent and the (E) curing agent" is the value obtained by adding up all the values ​​obtained by dividing the mass of the non-volatile components of the active ester curing agent and the curing agent present in the resin composition by the active group equivalent. By making the ratio of the amount of the (B) component and the (E) component to the epoxy resin within the above range, the effect of the present invention can be significantly obtained.

[0107] When a curing agent is contained as the (E) component, the amount ratio of the epoxy resin to the total (E) curing agent is preferably in the range of 1:0.01 to 1:1, more preferably 1:0.03 to 1:0.5, and even more preferably 1:0.05 to 1:0.1, in terms of the ratio of [the total number of epoxy groups of the epoxy resin]:[the total number of active groups of the (E) curing agent]. Here, the "active group number of the (E) curing agent" is the value obtained by adding up all the values ​​obtained by dividing the mass of the non-volatile component of the (E) curing agent present in the resin composition by the active group equivalent. By making the amount ratio of the epoxy resin to the curing agent as the (E) component within the above range, the effect of the present invention can be significantly obtained.

[0108] For the content of (E) curing agent, from the viewpoint of significantly obtaining the desired effect of the present invention, when the non-volatile component in the resin composition is set to 100% by mass, it is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and more preferably 0.3% by mass or more. The upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, and more preferably 1% by mass or less.

[0109] When the content of the component (B) when the non-volatile component in the resin composition is 100% by mass is b1, the content of the component (C) when the non-volatile component in the resin composition is 100% by mass is c1, and the content of the component (E) when the non-volatile component in the resin composition is 100% by mass is e1, b1 / (c1+e1) is preferably 1 or more, more preferably 2 or more, further preferably 3 or more, preferably 30 or less, more preferably 20 or less, further preferably 15 or less. By setting b1 / (c1+e1) within the above range, a cured product can be obtained that can reduce the dielectric loss tangent and has excellent contamination removability and adhesion.

[0110] <(F) Thermoplastic resin>

[0111] The resin composition may further contain (F) a thermoplastic resin as an arbitrary component in addition to the above-mentioned components.

[0112] As the thermoplastic resin of component (F), for example, phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamide-imide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene oxide resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. can be mentioned. Among them, phenoxy resin is preferred from the viewpoint of significantly obtaining the desired effect of the present invention. In addition, the thermoplastic resin can be used alone or in combination of two or more.

[0113] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenol acetophenone skeleton, phenolic skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0114] Specific examples of phenoxy resins include: "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumitomo Metal Chemicals; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290" and "YL7482" manufactured by Mitsubishi Chemical Corporation; and the like.

[0115] Examples of the polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred. Specific examples of the polyvinyl acetal resin include: "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LECBH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.; and the like.

[0116] Specific examples of polyimide resins include "RIKACOAT SN20" and "RIKACOAT PN20" manufactured by Shin Nippon Chemical Co., Ltd. Specific examples of polyimide resins include linear polyimides obtained by reacting difunctional hydroxy-terminated polybutadiene, a diisocyanate compound, and a tetrabasic acid anhydride (polyimides described in Japanese Patent Application Publication No. 2006-37083), polyimides containing a polysiloxane skeleton (polyimides described in Japanese Patent Application Publication No. 2002-12667 and Japanese Patent Application Publication No. 2000-319386, etc.), and the like.

[0117] Specific examples of polyamideimide resins include "VYLOMAX HR11NN" and "VYLOMAX HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamideimide resins include modified polyamideimides such as "KS9100" and "KS9300" (polyamideimide containing a polysiloxane skeleton) manufactured by Hitachi Chemical Co., Ltd.

[0118] Specific examples of the polyethersulfone resin include "PES5003P" manufactured by Sumitomo Chemical Co., Ltd. and the like.

[0119] Specific examples of the polyphenylene ether resin include oligophenylene ether-styrene resin "OPE-2St 1200" manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0120] Specific examples of the polysulfone resin include polysulfone "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0121] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the (F) thermoplastic resin is preferably 8,000 or more, more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 70,000 or less, more preferably 60,000 or less, particularly preferably 50,000 or less.

[0122] The content of the (F) thermoplastic resin is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more, and is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, based on 100% by mass of the non-volatile component in the resin composition, from the viewpoint of significantly obtaining the desired effect of the present invention.

[0123] <(G) Curing accelerator>

[0124] The resin composition may further contain (G) a curing accelerator as an arbitrary component in addition to the above-mentioned components.

[0125] Examples of curing accelerators include phosphorus curing accelerators, amine curing accelerators, imidazole curing accelerators, guanidine curing accelerators, and metal curing accelerators. Among them, phosphorus curing accelerators, amine curing accelerators, imidazole curing accelerators, and metal curing accelerators are preferred, and amine curing accelerators, imidazole curing accelerators, and metal curing accelerators are more preferred. One curing accelerator may be used alone, or two or more may be used in combination.

[0126] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.

[0127] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, and 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene are preferred.

[0128] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4 imidazole compounds such as -diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, isocyanuric acid adduct of 2-phenylimidazole, isocyanuric acid adduct of 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins, preferably 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole.

[0129] As the imidazole-based curing accelerator, a commercially available item may be used, and examples thereof include "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0130] Examples of the guanidine-based curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine. Preferred examples include dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene.

[0131] As metal curing accelerators, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. As specific examples of organic metal complexes, organic cobalt complexes such as cobalt acetylacetonate (II), cobalt acetylacetonate (III), organic copper complexes such as copper acetylacetonate (II), organic zinc complexes such as zinc acetylacetonate (II), organic iron complexes such as iron acetylacetonate (III), organic nickel complexes such as nickel acetylacetonate (II), and organic manganese complexes such as manganese acetylacetonate (II) can be cited. As organic metal salts, for example, zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.

[0132] From the viewpoint of significantly obtaining the desired effect of the present invention, the content of the curing accelerator (G) is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and further preferably 0.05% by mass or more, and is preferably 0.3% by mass or less, more preferably 0.2% by mass or less, and further preferably 0.1% by mass or less, based on 100% by mass of the non-volatile component in the resin composition.

[0133] <(H) Other additives>

[0134] The resin composition may further contain other additives as arbitrary components in addition to the above-mentioned components. Examples of such additives include organic fillers, resin additives such as thickeners, defoamers, leveling agents, and adhesion-imparting agents, etc. These additives may be used alone or in combination of two or more.

[0135] <Physical properties and uses of resin composition>

[0136] The cured product obtained by thermally curing the resin composition at 100°C for 30 minutes and then thermally curing it at 170°C for 30 minutes shows excellent stain removability. Therefore, when a through hole is formed in the cured product, an insulating layer with a maximum stain length of less than 5 μm at the bottom of the through hole can be formed. The stain removability can be measured by the method described in the examples described later.

[0137] The cured product obtained by thermally curing the resin composition at 190° C. for 90 minutes shows the characteristic of low dielectric loss tangent. Therefore, the aforementioned cured product can form an insulating layer with low dielectric loss tangent. As the dielectric loss tangent, it is preferably less than 0.013, more preferably less than 0.011 and less than 0.009. On the other hand, the lower limit of the dielectric loss tangent is not particularly limited, and can be 0.001 or more. The evaluation of the aforementioned dielectric loss tangent can be measured according to the method described in the embodiments described later.

[0138] The cured product obtained by thermally curing the resin composition at 100°C for 30 minutes, at 170°C for 30 minutes, and then at 200°C for 90 minutes shows excellent adhesion (peel strength) with copper foil. Therefore, the aforementioned cured product can form an insulating layer with excellent adhesion with copper foil. As the adhesion with copper foil, it is preferably more than 0.5kgf / cm, more preferably more than 0.6kgf / cm, and further preferably more than 0.7kgf / cm. On the other hand, the upper limit of adhesion is not particularly limited, and can be less than 5kgf / cm, etc. The evaluation of the aforementioned adhesion can be measured according to the method described in the embodiments described later.

[0139] The resin composition of the present invention can form an insulating layer that can reduce dielectric loss tangent, has excellent adhesion, and is also excellent in stain removal. Therefore, the resin composition of the present invention can be suitably used as a resin composition for insulating purposes. Specifically, it can be suitably used as: a resin composition for forming an insulating layer (resin composition for forming an insulating layer for forming a conductor layer), the insulating layer is an insulating layer for forming a conductor layer (including a rewiring layer), and the conductor layer is formed on the insulating layer.

[0140] In addition, in the multilayer printed wiring board described later, it can be suitably used as: a resin composition for forming an insulating layer of a multilayer printed wiring board (resin composition for forming an insulating layer of a multilayer printed wiring board), and a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for forming an interlayer insulating layer of a printed wiring board).

[0141] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can also be suitably used as a resin composition for a rewiring forming layer (resin composition for forming a rewiring forming layer) as an insulating layer for forming a rewiring layer, and a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When manufacturing a semiconductor chip package, a rewiring layer can be further formed on the sealing layer;

[0142] (1) Step of laminating a temporary fixing film on a substrate,

[0143] (2) a step of temporarily fixing the semiconductor chip on the temporary fixing film,

[0144] (3) a step of forming a sealing layer on a semiconductor chip,

[0145] (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip,

[0146] (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off, and

[0147] (6) A step of forming a rewiring layer as a conductive layer on the rewiring formation layer.

[0148] Furthermore, the resin composition of the present invention can form an insulating layer having good component embedding properties, and therefore can be preferably used when the printed wiring board is a component-embedded wiring board.

[0149] [Resin sheet]

[0150] The resin sheet of the present invention comprises a support and a resin composition layer formed from the resin composition of the present invention and provided on the support.

[0151] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, and further preferably 30 μm or less, from the viewpoint of thinning the printed wiring board and providing a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be 5 μm or more, 10 μm or more, etc.

[0152] Examples of the support include films made of plastic materials, metal foils, and release papers, and films made of plastic materials and metal foils are preferred.

[0153] When a film formed of a plastic material is used as a support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0154] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. The copper foil may be a foil made of a single metal of copper or an alloy of copper and other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).

[0155] The surface of the support to be in contact with the resin composition layer may be subjected to matte treatment, corona treatment, or antistatic treatment.

[0156] In addition, as a support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As a release agent used in the release layer of a support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins can be cited. The support with a release layer can use commercial products, for example: as a PET film having a release layer with an alkyd resin-based release agent as the main component, "SK-1", "AL-5", "AL-7" made by Lindeco, "Lumirror T60" made by Toray, "Purex" made by Teijin, "Unipeel" made by UNITIKA, etc.

[0157] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.

[0158] In one embodiment, the resin sheet may further include other layers as needed. As the other layers, for example, a protective film selected according to the support body and disposed on the surface of the resin composition layer that is not bonded to the support body (i.e., the surface on the opposite side of the support body) can be cited. The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, dust and the like can be prevented from adhering to the surface of the resin composition layer or from being damaged on the surface of the resin composition layer.

[0159] The resin sheet can be produced, for example, by preparing a resin varnish obtained by dissolving a resin composition in an organic solvent, applying the resin varnish on a support using a die coater or the like, and drying the varnish to form a resin composition layer.

[0160] Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone (MEK) and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate (cellosolve acetate), propylene glycol monomethyl ether acetate and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; amide solvents such as dimethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone, etc. The organic solvent may be used alone or in combination of two or more.

[0161] Drying can be carried out by known methods such as heating and blowing hot air. The drying conditions are not particularly limited, and the drying is carried out in a manner such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying conditions also vary depending on the boiling point of the organic solvent in the resin varnish. For example, when using a resin varnish containing 30% to 60% by mass of an organic solvent, the resin composition layer can be formed by drying at 50° C. to 150° C. for 3 minutes to 10 minutes.

[0162] The resin sheet can be stored by winding it into a roll. When the resin sheet has a protective film, the protective film can be peeled off before use.

[0163] [Printed wiring board]

[0164] The printed wiring board of the present invention includes an insulating layer formed of a cured product of the resin composition of the present invention.

[0165] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet and by a method including the following steps (I) and (II):

[0166] (I) a step of laminating a resin sheet on the inner substrate so that the resin composition layer of the resin sheet is bonded to the inner substrate;

[0167] (II) A step of thermally curing the resin composition layer to form an insulating layer.

[0168] The "inner substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, thermosetting polyphenylene ether substrates, etc. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of the substrate is sometimes referred to as an "inner circuit substrate". In addition, an intermediate product to be further formed with an insulating layer and / or a conductor layer when manufacturing a printed wiring board is also included in the "inner substrate" referred to in the present invention. In the case where the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components can be used.

[0169] The lamination of the inner substrate and the resin sheet can be performed, for example, by heat-pressing the resin sheet to the inner substrate from the support body side. As a component for heat-pressing the resin sheet to the inner substrate (hereinafter also referred to as "heat-pressing component"), for example, a heated metal plate (SUS end plate (mirror plate) etc.) or a metal roller (SUS roller) etc. can be cited. It should be noted that it is preferred not to press the heat-pressing component directly on the resin sheet, but to press it through an elastic material such as heat-resistant rubber so that the resin sheet fully follows the surface unevenness of the inner substrate.

[0170] The lamination of the inner substrate and the resin sheet can be implemented by vacuum lamination. In the vacuum lamination method, the heating and pressing temperature is preferably 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heating and pressing pressure is preferably 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heating and pressing time is preferably 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably implemented under reduced pressure conditions with a pressure of 26.7hPa or less.

[0171] Lamination can be performed using a commercially available vacuum laminator. Examples of commercially available vacuum laminators include a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a vacuum applicator manufactured by Nikko-Materials Co., Ltd., and a batch vacuum pressure laminator.

[0172] After lamination, the laminated resin sheet can be smoothed by, for example, pressing the heating and pressing member from the support side under normal pressure (atmospheric pressure). The pressing conditions for the smoothing treatment can be set to the same conditions as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed using a commercially available laminator. It should be noted that the lamination and smoothing treatment can be performed continuously using the above-mentioned commercially available vacuum laminator.

[0173] The support may be removed between step (I) and step (II), or may be removed after step (II).

[0174] In step (II), the resin composition layer is thermally cured to form an insulating layer. The thermal curing conditions of the resin composition layer are not particularly limited, and conditions generally used when forming an insulating layer of a printed wiring board can be used.

[0175] For example, the thermal curing conditions of the resin composition layer vary depending on the type of the resin composition, and the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.

[0176] The resin composition layer may be preheated at a temperature lower than the curing temperature before the resin composition layer is thermally cured. For example, the resin composition layer may be preheated at a temperature of 50°C or higher and lower than 120°C (preferably 60°C or higher and 115°C or lower, more preferably 70°C or higher and 110°C or lower) for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and further preferably 15 minutes to 100 minutes) before the resin composition layer is thermally cured.

[0177] When manufacturing a printed wiring board, the process of (III) opening a hole in the insulating layer, the process of (IV) roughening the insulating layer, and the process of (V) forming a conductor layer can be further implemented. These processes (III) to (V) can be implemented according to various methods known to those skilled in the art used in the manufacture of printed wiring boards. It should be noted that, when the support body is removed after process (II), the removal of the support body can be implemented between process (II) and process (III), between process (III) and process (IV), or between process (IV) and process (V). In addition, as needed, the formation of the insulating layer and the conductor layer of process (II) to process (V) can also be repeatedly implemented to form a multilayer wiring board.

[0178] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as through holes and vias in the insulating layer. Step (III) can be performed using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.

[0179] Step (IV) is a step of roughening the insulating layer. Usually, contamination is also removed in step (IV). There are no particular restrictions on the steps and conditions of the roughening treatment, and the known steps and conditions commonly used when forming the insulating layer of the printed wiring board can be adopted. For example, swelling treatment using a swelling solution, roughening treatment using an oxidant, and neutralization treatment using a neutralizing solution can be sequentially implemented to roughen the insulating layer. There are no particular restrictions on the swelling solution used for the roughening treatment, and alkali solutions, surfactant solutions, etc. can be cited, preferably alkali solutions, and more preferably sodium hydroxide solutions and potassium hydroxide solutions as the alkali solutions. As commercially available swelling solutions, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan Co., Ltd. can be cited. The swelling treatment using a swelling solution is not particularly limited, and for example, it can be performed by immersing the insulating layer in a swelling solution at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling solution at 40°C to 80°C for 5 minutes to 15 minutes. As an oxidant for roughening treatment, there is no particular limitation, and an alkaline permanganate solution formed by dissolving potassium permanganate and sodium permanganate in an aqueous solution of sodium hydroxide can be cited. The roughening treatment performed using an oxidant such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidant solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. As commercially available oxidants, alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securiganth P" manufactured by Atotech Japan Co., Ltd. can be cited. In addition, as the neutralizing solution used for the roughening treatment, an acidic aqueous solution is preferred, and as a commercially available product, for example, "Reduction Solution Securiganth P" manufactured by Atotech Japan Co., Ltd. can be cited. The treatment with the neutralizing solution can be performed by immersing the treated surface after the roughening treatment with the oxidizing agent in the neutralizing solution at 30°C to 80°C for 5 minutes to 30 minutes. In view of operability, etc., it is preferred to immerse the object after the roughening treatment with the oxidizing agent in the neutralizing solution at 40°C to 70°C for 5 minutes to 20 minutes.

[0180] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment is preferably less than 400nm, more preferably less than 350nm, and more preferably less than 300nm. There is no particular restriction on the lower limit, and it can be preferably more than 0.5nm, more preferably more than 1nm, etc. In addition, the root mean square roughness (Rq) of the insulating layer surface after roughening treatment is preferably less than 400nm, more preferably less than 350nm, and more preferably less than 300nm. There is no particular restriction on the lower limit, and it can be preferably more than 0.5nm, more preferably more than 1nm, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0181] Step (V) is a step of forming a conductor layer, and a conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer can be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above group (for example, nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy) can be cited. Among them, from the perspectives of versatility, cost, ease of patterning, etc., a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is further preferred.

[0182] The conductor layer may be a single-layer structure or a multilayer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. When the conductor layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0183] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is usually 3 μm to 35 μm, preferably 5 μm to 30 μm.

[0184] In one embodiment, the conductor layer can be formed by plating. For example, the surface of the insulating layer can be plated using a conventionally known technique such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. From the perspective of manufacturing simplicity, it is preferably formed using a semi-additive method. An example of forming a conductor layer using a semi-additive method is shown below.

[0185] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. A metal layer is formed on the exposed plating seed layer by electrolytic plating, and then the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching, etc., so that a conductor layer having a desired wiring pattern can be formed.

[0186] [Semiconductor devices]

[0187] The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be produced using the printed wiring board of the present invention.

[0188] Examples of the semiconductor device include various semiconductor devices used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and airplanes).

[0189] The semiconductor device of the present invention can be manufactured by mounting a component (semiconductor chip) at a conductive position of a printed wiring board. The so-called "conductive position" refers to "a position in a printed wiring board that conducts an electrical signal", and the position may be either a surface or a buried position. In addition, the semiconductor chip is not particularly limited as long as it is an electrical circuit element made of semiconductor.

[0190] The method for mounting a semiconductor chip when manufacturing a semiconductor device is not particularly limited as long as the semiconductor chip can function effectively. Specifically, there are wire bonding mounting methods, flip chip mounting methods, mounting methods based on bump less build-up layers (BBUL), mounting methods based on anisotropic conductive films (ACF), mounting methods based on non-conductive films (NCF), etc. The so-called "mounting method based on bump less build-up layers (BBUL)" here refers to "a mounting method in which a semiconductor chip is directly embedded in a recess of a printed wiring board to connect the semiconductor chip to the wiring on the printed wiring board".

[0191] Example

[0192] The present invention is specifically described below by showing examples. However, the present invention is not limited to the following examples. In the following description, unless otherwise clearly stated, the "parts" and "%" indicating the amount refer to "parts by mass" and "mass %" respectively. In addition, unless otherwise clearly stated, the operations described below are performed under normal temperature and pressure.

[0193] <Synthesis Example 1: Synthesis of polyester polyol resin A having an aromatic structure>

[0194] 779.1 parts by mass of bisphenol A glycol ether (HYPROX MDB-561, manufactured by DIC Corporation), 132.9 parts by mass of isophthalic acid, and 40.4 parts by mass of sebacic acid were placed in the reaction apparatus, and heating and stirring were started. Next, after the internal temperature was raised to 230°C, 0.10 parts by mass of tetraisopropyl titanate was placed, and the reaction was carried out at 230°C for 24 hours to synthesize a polyester polyol resin A having an aromatic structure. The obtained polyester polyol resin A having an aromatic structure had a hydroxyl value of 36.9 mgKOH / g, a number average molecular weight of 3040, a glass transition temperature of -14°C, and a viscosity of 9 Pa·s at 75°C.

[0195] <Synthesis Example 2: Synthesis of polyester polyol resin B>

[0196] 395.6 parts by mass of ethylene glycol and 838.8 parts by mass of adipic acid were added to the reaction device, and heating and stirring were started. Next, after the internal temperature was raised to 220°C, 0.03 parts by mass of tetraisopropyl titanate was added, and the reaction was carried out at 220°C for 24 hours to synthesize polyester polyol resin B. The obtained polyester polyol resin B had a hydroxyl value of 56.2 mgKOH / g, a number average molecular weight of 2000, a viscosity of 0.6 Pa·s at 75°C, and did not show a glass transition temperature.

[0197] <Example 1>

[0198] 20 parts of a bisphenol epoxy resin ("ZX1059" manufactured by NIPPON STEEL Chemical & Material Co., Ltd.) and 40 parts of a biphenyl epoxy resin ("NC3000L" manufactured by Nippon Kayaku) were dissolved in 20 parts of MEK (methyl ethyl ketone). Thereto were added 330 parts of spherical silica (average particle size 0.77 μm, “SO-C2” manufactured by Yaduma Co., Ltd.) surface-treated with an amine-based alkoxysilane compound (“KBM573” manufactured by Shin-Etsu Chemical Co., Ltd.), 90 parts of an active ester-based curing agent (“HPC-8000-65T” manufactured by DIC Corporation, a toluene solution having a solid content of 60% by mass), 5 parts of a triazine-containing cresol novolac resin (“LA-3018-50P” manufactured by DIC Corporation, a methoxypropanol solution having a solid content of 50% by mass), 5 parts of a phenoxy resin (“YX7553BH30” manufactured by Mitsubishi Chemical Corporation, a MEK / cyclohexanone solution having a solid content of 30% by mass), 5 parts of the polyester polyol resin A obtained in Synthesis Example 1, and 0.1 parts of 4-dimethylaminopyridine (manufactured by Wako Pure Chemical Industries, Ltd., abbreviated as “DMAP”), and the mixture was uniformly dispersed using a high-speed rotary mixer to prepare a resin varnish.

[0199] As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) having a release layer was prepared. The aforementioned resin varnish was evenly applied to the release layer of the support so that the thickness of the resin composition layer after drying was 40 μm. Then, the resin varnish was dried at 80° C. to 100° C. (average 90° C.) for 4 minutes to obtain a resin sheet including a support and a resin composition layer.

[0200] <Example 2>

[0201] In Example 1,

[0202] 40 parts of biphenyl epoxy resin (manufactured by Nippon Kayaku Co., Ltd., NC3000L) were replaced with 40 parts of naphthol epoxy resin (manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., ESN475V).

[0203] The amount of active ester curing agent (DIC Corporation, HPC-8000-65T) was changed from 90 parts to 85 parts;

[0204] Resin composition 2 was prepared in the same manner as in Example 1 except for the above matters.

[0205] <Example 3>

[0206] In Example 1, 90 parts of active ester curing agent (manufactured by DIC Corporation, HPC-8000-65T) was replaced with 95 parts of active ester curing agent (manufactured by DIC Corporation, HPC-8150-62T);

[0207] Resin composition 3 was prepared in the same manner as in Example 1 except for the above matters.

[0208] <Example 4>

[0209] In Example 1, 90 parts of active ester curing agent (manufactured by DIC Corporation, HPC-8000-65T) was replaced with 90 parts of active ester curing agent (manufactured by DIC Corporation, HPC-8000L-65TM);

[0210] Resin composition 4 was prepared in the same manner as in Example 1 except for the above matters.

[0211] <Example 5>

[0212] In Example 3, the amount of polyester polyol resin A having an aromatic structure was changed from 5 parts to 10 parts, and the amount of inorganic filler (SO-C2 manufactured by Yaduma Co., Ltd.) was changed from 330 parts to 340 parts. Resin composition 5 was prepared in the same manner as in Example 3 except for the above matters.

[0213] <Example 6>

[0214] In Example 3, the amount of the polyester polyol resin A having an aromatic structure was changed from 5 parts to 2.5 parts. A resin composition 6 was prepared in the same manner as in Example 3 except for the above matters.

[0215] <Example 7>

[0216] In Example 3,

[0217] The amount of active ester curing agent (DIC Corporation, HPC-8150-62T) was changed from 95 parts to 60 parts.

[0218] The amount of inorganic filler (SO-C2 manufactured by Yaduma Co., Ltd.) was changed from 330 parts to 270 parts.

[0219] The amount of polyester polyol resin A was changed from 5 parts to 4 parts;

[0220] A resin composition 7 was prepared in the same manner as in Example 3 except for the above matters.

[0221] <Comparative Example 1>

[0222] In Example 1, 5 parts of the polyester polyol resin A having an aromatic structure was replaced with 5 parts of the polyester polyol resin B. A resin composition 8 was prepared in the same manner as in Example 1 except for the above matters.

[0223] <Comparative Example 2>

[0224] In Example 1, 5 parts of the polyester polyol resin A having an aromatic structure was replaced with 5 parts of an epoxy resin having a butadiene structure (PB3600 manufactured by Daicel Corporation). Resin composition 9 was prepared in the same manner as in Example 1 except for the above matters.

[0225] <Comparative Example 3>

[0226] In Example 1, 5 parts of the polyester polyol resin A having an aromatic structure was not used. A resin composition 10 was prepared in the same manner as in Example 1 except for the above matters.

[0227] <Evaluation of stain removability>

[0228] (1) Base treatment of internal substrate:

[0229] As the inner substrate, a glass cloth-based epoxy resin double-sided copper-clad laminate with copper foil on the surface was prepared (the thickness of the copper foil was 18 μm, the thickness of the substrate was 0.8 mm, "R1515A" manufactured by Panasonic). The copper foil on the surface of the inner substrate was etched with a copper etching amount of 1 μm using a microetchant ("CZ8101" manufactured by MEC) to perform a roughening treatment. Then, it was dried at 190°C for 30 minutes.

[0230] (2) Lamination and curing of resin sheets:

[0231] Using an intermittent vacuum pressurized laminator (Nikko-Materials Co., Ltd., 2-stage stacking laminator "CVP700"), the resin sheets obtained in the above-mentioned embodiments and comparative examples are laminated on both sides of the inner substrate in such a manner that the resin composition layer is bonded to the aforementioned inner substrate. The lamination is implemented in the following manner: decompression is performed for 30 seconds to make the air pressure below 13 hPa, and then crimping is performed at a temperature of 100°C and a pressure of 0.74 MPa for 30 seconds. Next, the laminated resin sheet is hot-pressed at atmospheric pressure at 100°C and a pressure of 0.5 MPa for 60 seconds to make it smooth. Then, it is placed in an oven at 100°C and heated for 30 minutes, and then moved to an oven at 170°C and heated for 30 minutes.

[0232] (3) Through-hole formation:

[0233] The insulating layer was processed using a CO2 laser processing machine (LK-2K212 / 2C) manufactured by Via Mechanics Co., Ltd. at a frequency of 2000 Hz, a pulse width of 3 μs, an output power of 0.95 W, and an irradiation (shot) number of 3, to form a through hole with a top diameter (diameter) of 50 μm on the surface of the insulating layer and a diameter of 50 μm on the bottom surface of the insulating layer. Then, the support body was peeled off to obtain a circuit board.

[0234] (4) Roughening treatment:

[0235] The circuit board was immersed in Swelling DipSecuriganth P manufactured by Atotech Japan Co., Ltd. as a swelling solution at 60°C for 10 minutes. Next, it was immersed in Concentrate Compact P (KMnO4: 60 g / L, NaOH: 40 g / L aqueous solution) manufactured by Atotech Japan Co., Ltd. as a roughening solution at 80°C for 25 minutes. Finally, it was immersed in Reduction SolutionSecuriganth P manufactured by Atotech Japan Co., Ltd. as a neutralizing solution at 40°C for 5 minutes.

[0236] (5) Evaluation of contamination removal properties (evaluation of residue at the bottom of through-holes):

[0237] The area around the bottom of the through hole was observed using a scanning electron microscope (SEM), and the maximum contamination length from the wall surface of the bottom of the through hole was measured from the obtained image, and evaluated according to the following criteria:

[0238] ○: Maximum contamination length is less than 5μm

[0239] ×: The maximum contamination length is 5 μm or more.

[0240] <Measurement of dielectric loss tangent>

[0241] The resin sheets obtained in the above-mentioned examples and comparative examples were cured in an oven at 190°C for 90 minutes and then peeled from the support to obtain a cured product. The cured product was cut into a size of 80 mm in length and 2 mm in width as an evaluation sample. For the evaluation sample, the dielectric loss tangent was measured using the HP8362B device manufactured by Agilent Technologies using the resonant cavity perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C. The measurement was performed on two test pieces and the average value was calculated.

[0242] <Measurement of copper foil adhesion (peel strength)>

[0243] (Preparation of substrate for adhesion evaluation)

[0244] As the inner substrate, a glass cloth-based epoxy resin double-sided copper-clad laminate with copper foil on the surface was prepared (the thickness of the copper foil was 18 μm, the thickness of the substrate was 0.8 mm, "R1515A" manufactured by Panasonic Corporation). The copper foil on the surface of the inner substrate was completely etched away. Then, it was dried at 190° C. for 30 minutes.

[0245] The resin sheets obtained in the above-mentioned examples and comparative examples were laminated on both sides of the inner substrate using an intermittent vacuum pressurizing laminator (Nikko-Materials Co., Ltd., 2-stage stacking laminator "CVP700") in such a manner that the resin composition layer was bonded to the aforementioned inner substrate. The lamination was performed by reducing the pressure for 30 seconds to a pressure of 13 hPa or less, and then pressing for 30 seconds at a temperature of 100°C and a pressure of 0.74 MPa.

[0246] Next, the laminated resin sheets were smoothed by heat pressing at 100°C and 0.5 MPa for 60 seconds under atmospheric pressure. The support was then peeled off to obtain an "intermediate multilayer body I" comprising a resin composition layer, an inner substrate, and a resin composition layer in this order.

[0247] On the other hand, a copper foil having a glossy surface (thickness 35 μm, "3EC-III" manufactured by Mitsui Metals Co., Ltd.) was prepared. The glossy surface of the copper foil was etched with a copper etching amount of 1 μm using a microetchant ("CZ8101" manufactured by MEC Corporation) to perform a roughening treatment. The copper foil obtained in the above manner is referred to as "roughened copper foil".

[0248] The roughened copper foil is laminated on both sides of the intermediate multilayer body I in such a manner that the surface of the roughened copper foil is bonded to the resin composition layer of the intermediate multilayer body I. The lamination is performed under the same conditions as the lamination of the resin sheet to the inner substrate. Thus, an "intermediate multilayer body II" is obtained which sequentially includes a roughened copper foil, a resin composition layer, an inner substrate, a resin composition layer, and a roughened copper foil.

[0249] The intermediate multilayer body II was placed in an oven at 100°C and heated for 30 minutes, then moved to an oven at 170°C and heated for 30 minutes. Next, the intermediate multilayer body II was taken out of the oven to room temperature, and then placed in an oven at 200°C and heated for an additional 90 minutes. Thus, the resin composition layer was thermally cured to obtain an "evaluation substrate A" comprising a roughened copper foil, an insulating layer as a cured product of the resin composition layer, an inner substrate, an insulating layer as a cured product of the resin composition layer, and a roughened copper foil. In the evaluation substrate A, the roughened copper foil is equivalent to the conductor layer.

[0250] (Measurement of Copper Foil Adhesion (Peel Strength))

[0251] The peel strength between the roughened copper foil and the insulating layer was measured using the aforementioned evaluation substrate A. The peel strength was measured in accordance with JIS C6481. Specifically, the peel strength was measured by the following operation.

[0252] On the roughened copper foil of the evaluation substrate A, a cut is formed to surround a rectangular portion with a width of 10 mm and a length of 100 mm. One end of the rectangular portion is peeled off and clamped with a clamp (manufactured by TSE Co., Ltd., AUTO COM type tester "AC-50C-SL"). The rectangular portion is peeled off in the vertical direction within a range of 35 mm in length, and the load (kgf / cm) during the peeling is measured as the peeling strength. The peeling is performed at a speed of 50 mm / min at room temperature.

[0253] [Table 1]

[0254]

[0255] In Examples 1 to 7, even when the components (E) to (G) were not contained, it was confirmed that the same results as those of the above-mentioned Examples were obtained, although there were differences in degree.

Claims

1. A resin composition comprising: (A) Epoxy resin, (B) active ester curing agent, (C) a polyester polyol resin having an aromatic structure, and (D) Inorganic filling materials, When the nonvolatile component in the resin composition is 100 mass %, the content of the component (A) is 1 mass % or more and 25 mass % or less, When the nonvolatile component in the resin composition is 100 mass %, the content of the component (D) is 50 mass % or more and 90 mass % or less, When b1 represents the content of the component (B) when the nonvolatile component in the resin composition is 100 mass %, and c1 represents the content of the component (C) when the nonvolatile component in the resin composition is 100 mass %, b1 / c1 is 3 or more and 30 or less.

2. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (A) is 10% by mass or more.

3. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (A) is 15% by mass or less.

4. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (B) is 1 mass % or more.

5. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 5% by mass or more.

6. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 30% by mass or less.

7. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 15% by mass or less.

8. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (C) is 0.1 mass % or more and 10 mass % or less.

9. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 1% by mass or more.

10. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 1.5% by mass or less.

11. The resin composition according to claim 1, wherein The component (C) has a bisphenol skeleton.

12. The resin composition according to claim 1, wherein The component (C) has a hydroxyl group at the terminal.

13. The resin composition according to claim 1, wherein The hydroxyl value of the component (C) is 2 mgKOH / g or more and 450 mgKOH / g or less.

14. The resin composition according to claim 1, wherein The hydroxyl value of the component (C) is 35 mgKOH / g or more.

15. The resin composition according to claim 1, wherein The hydroxyl value of the component (C) is 40 mgKOH / g or less.

16. The resin composition according to claim 1, wherein The viscosity of the component (C) at 75°C is 0.5 Pa·s or more and 25 Pa·s or less.

17. The resin composition according to claim 1, wherein The viscosity of the component (C) at 75°C is 5 Pa·s or more.

18. The resin composition according to claim 1, wherein The viscosity of the component (C) at 75°C is 15 Pa·s or less.

19. The resin composition according to claim 1, wherein The number average molecular weight of the component (C) is 500 or more and 7000 or less.

20. The resin composition according to claim 1, wherein The number average molecular weight of the component (C) is 2500 or more.

21. The resin composition according to claim 1, wherein The number average molecular weight of the component (C) is 5,000 or less.

22. The resin composition according to claim 1, wherein The component (B) contains at least one selected from the group consisting of a dicyclopentadiene-type active ester curing agent and a naphthalene-type active ester curing agent.

23. The resin composition according to claim 1, wherein When the content of the component (B) when the nonvolatile component in the resin composition is 100 mass % is b1 and the content of the component (C) when the nonvolatile component in the resin composition is 100 mass % is c1, b1 / c1 is 5 or more.

24. The resin composition according to claim 1, wherein When the content of the component (B) when the nonvolatile component in the resin composition is 100 mass % is b1 and the content of the component (C) when the nonvolatile component in the resin composition is 100 mass % is c1, b1 / c1 is 20 or less.

25. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (D) is 70% by mass or more.

26. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (D) is 75 mass % or less. 27 . The resin composition according to claim 1 , further comprising (E) a curing agent, wherein the (E) curing agent does not include the (B) active ester curing agent.

28. The resin composition according to claim 27, wherein (E) The curing agent includes a phenolic curing agent.

29. The resin composition according to claim 27, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (E) is 0.1 mass % or more.

30. The resin composition according to claim 27, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (E) is 0.3 mass % or more.

31. The resin composition according to claim 27, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the component (E) is 5 mass % or less.

32. The resin composition according to claim 27, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the (E) component is 1 mass % or less.

33. The resin composition according to claim 1, which is used for insulation purposes.

34. The resin composition according to claim 1, which is used for forming an insulating layer.

35. The resin composition according to claim 1, which is used to form an insulating layer, and the insulating layer is an insulating layer for forming a conductor layer.

36. A resin sheet comprising: Support body, and A resin composition layer provided on the support and comprising the resin composition according to any one of claims 1 to 35. 37 . A printed wiring board comprising an insulating layer formed using a cured product of the resin composition according to claim 1 .

38. A semiconductor device comprising the printed wiring board according to claim 37.

Citation Information

Patent Citations

  • Silicone-containing polyimide resin, silicone-containing polyamic acid and their production

    JP2000319386A

  • Polyimidesilicone resin, solution composition thereof, and polyimidesilicone resin coating film

    JP2002012667A

  • Thermosetting resin composition containing modified polyimide resin

    JP2006037083A

  • Curable resin composition

    JP2014159512A

  • Epoxy resin modifying agent

    WO2019044803A1